PentaCOME 1000+ to Stop Stunting at Payangan District - Tanjung Subrata; Bayuningrat IGM.; Kartinawati KM; Pradnyawati LG; Wijaya MI; Pariartha IM; Indraningrat AAG; Wijaya MD; Sari LPEK (Community Development Journal, 2022)
In 2021, stunting is still 24.4% of the population in Indonesia, making it a significant public health issue. Gianyar Regency, which is under the supervision of the Warmadewa University Faculty of Medicine and Health Sciences (FKIK Unwar), has a stunting rate above the average for Bali province, which is 12.1%. Because of this, the PentaCOME 1000+ program, a collaboration of FKIK Unwar and the Ministry of Education and Culture of the Republic of Indonesia with business and industry partners (DUDI) PT. Sido Muncul Tbk., held in Payangan District Gianyar Regency on November 12 2022. The program engages all students through mentoring one student, one pregnant woman, her family, and their environment, couples of childbearing ages (PUS), prospective brides (catin), and development tourism (ecotourism). In addition to mentoring and educating the community, PT. Sido Muncul distributed additional nutrition in two standardized herbal forms: Sido Muncul Sari Daun Kelor, which is beneficial as supplemental nutrition for pregnant women, and Sido Muncul Suprasi, which contains katuk leaves, which are beneficial for nursing mothers. There were 417 pregnant and lactating women, of which 39.6% were between the ages of 26 and 30; 52% have completed public high school (SMU); 41.5% work as housewives; and 70% have a monthly income of less than two million rupiah, which is below the Gianyar UMK. In Payangan District, the greatest risk factor for stunting is a family income below the UMK. It is anticipated that the PentaCOME 1000+ program will improve the quality of maternal and infant health in Payangan District